Cyclodimers and cyclotrimers of 2,3 -bisalkynylated anthracenes, phenazines and diazatetracenes - Maier, Steffen; Hippchen, Nikolai; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2021)
The synthesis of novel (N−)acene-based cyclooligomers is reported. Glaser-Hay coupling of the bisethynylated monomers results in cyclodimers and cyclotrimers that are separable by column and gel-permeation chromatographies. For the diazatetracene, the use of sec-butyl-silylethynyl groups is necessary to achieve solubility. Diazatetracene-based cyclodimers and cyclotrimers were used as semiconductors in thin-film transistors. Although their optoelectronic properties are quite similar, their electron mobilities in proof-of-concept thin-film transistors differ by an order of magnitude.